Adaptive synchronization control with optimization policy for fractional-order chaotic systems between 0 and 1 and its application in secret communication. (September 2019) - Li, Rui-Guo; Wu, Huai-Ning
Abstract: For fractional-order chaotic systems with unequal orders between 0 and 1, a synchronization based on them and its application in secret communication are investigated in the presence of parameter uncertainty and unknown external disturbance. Firstly, through using fractional calculus theory and adaptive control method, we design a feedback controller to achieve the synchronization between the systems. Next, in order to make the controller better apply to secret communication, an optimization policy is provided for it by some performance indicator about state variables in the error system. Meanwhile, to further enhance the performance of the controller, we introduce an interval estimation (IE) strategy into quantum particle swarm optimization (QPSO) algorithm to improve it, and then this algorithm is used to optimize the controller parameters. In addition, for the security of signal transmission, a feedback mechanism with encrypted signal is offered in secret communication. Finally, by comparison, simulation experiments verify the validity and applicability of the proposed method. Highlights: An adaptive synchronization controller is designed between fractional-order systems. Develop an optimization policy on the controller to reduce the impact of disturbances. A QPSO algorithm with interval estimation is provided for controller optimization. Realize the communication by a signal feedback mechanism and the proposed controller.